Tense-aspect conditioned agent marking in Kanakanavu, an Austronesian language of Taiwan - Cheng Yi-Yang (Open Linguistics, 2023)
This article examines two types of lexical effects in the voice system of Kanakanavu, an Austronesian language of Taiwan. The first concerns a well-attested phenomenon in the Austronesian literature: interactions between the semantic transitivity of verbs and their ability (or lack thereof) to undergo voice alternation. The second concerns a phenomenon that is typologically and areally rare in the western Austronesian context – differential agent marking. The pronominal agent in Kanakanavu’s patient-/undergoer-voice construction is differentially case-marked depending on the tense-aspect value of the clause. However, lexical effects are found in how the differentially marked agent is interpreted. When dynamic verbs are used, omitted agents in perfective clauses are interpreted as coreferential with a specific referent mentioned in prior discourse, but those in non-perfective clauses are interpreted as having generic reference, backgrounded, and/or not centrally involved in the situation expressed by the verb. When stative verbs are used, alternation between perfective and imperfective verb forms may have various effects on the interpretation of the agent. In some stative verbs, the agent is interpreted as a prototypical semantic agent in the perfective, but as a semantic experiencer in the imperfective. In other stative verbs, the perfective/non-perfective alternation has to do with whether a change of state is involved, without having any effects on agent interpretation. This study explores how lexical effects manifest across both elicited and natural discourse data. It also presents the phenomenon of differential agent marking in Kanakanavu as neither typical nor representative in the western Austronesian context.